2007
DOI: 10.1182/blood-2007-03-082065
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for EKLF in megakaryocyte lineage commitment

Abstract: Megakaryocytes and erythroid cells are thought to derive from a common progenitor during hematopoietic differentiation. Although a number of transcriptional regulators are important for this process, they do not explain the bipotential result. We now show by gain-and loss-offunction studies that erythroid Krü ppellike factor (EKLF), a transcription factor whose role in erythroid gene regulation is well established, plays an unexpected directive role in the megakaryocyte lineage. EKLF inhibits the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
172
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(187 citation statements)
references
References 72 publications
14
172
1
Order By: Relevance
“…Given the restricted tissue specificity and temporal regulation of EKLF expression in vivo, it is possible that post-translational regulation and/or protein interactions govern which of the opposing roles EKLF plays in the cell divisions that lead to terminal erythroid differentiation. In addition, EKLF is expressed over a period that encompasses several different stages in hematopoiesis (21,22). Although Pilon et al (2) have demonstrated that EKLF binding to various sites on the genome is dynamic and dependent on differentiation stage, it is not clear which signals trigger these changes.…”
Section: Eklfmentioning
confidence: 99%
“…Given the restricted tissue specificity and temporal regulation of EKLF expression in vivo, it is possible that post-translational regulation and/or protein interactions govern which of the opposing roles EKLF plays in the cell divisions that lead to terminal erythroid differentiation. In addition, EKLF is expressed over a period that encompasses several different stages in hematopoiesis (21,22). Although Pilon et al (2) have demonstrated that EKLF binding to various sites on the genome is dynamic and dependent on differentiation stage, it is not clear which signals trigger these changes.…”
Section: Eklfmentioning
confidence: 99%
“…Although EKLF predominantly serves as a transcriptional activator, protein-protein interactions between EKLF and corepressors, such as mSin3A and HDAC1 [21], can result in the stage-specific repression of EKLF target genes [22]. Recent studies demonstrate that EKLF plays a novel role in negatively regulating megakaryocyte lineage commitment [23]. EKLF is also posttranslationally modified by phosphorylation [24], acetylation [16], ubiquitylation [25], and sumoylation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, KLF1 may use these repressors to silence conflicting differentiation programs to ensure that progenitor cells follow the erythropoietic lineage. In support of this, KLF1 null cells, which express neither KLF3 nor KLF8, show increased promiscuity toward the megakaryocyte lineage (43)(44)(45). The exact contribution of this KLF network to erythroid development will be revealed by comparative analysis of microarray and ChIP-Seq data from KLF1, KLF3, and KLF8 null tissue.…”
Section: Klf3 and Erythropoiesismentioning
confidence: 99%